Pengembangan Modul IPA Terpadu Problem-Based Learning (PBL) Dengan Tema Energi Sebagai Sumber Kehidupan SMP/MTs - Novyatun Latifah; Indica Yona Okyranida; Asep Setiadi (UNIVERSITAS INDRAPRASTA PGRI, 2020)
The purpose of the research is to design and develop an Integrated Science Module based on Problem-Based Learning (PBL), in addition, in addition, researchers also want to know the results of the student response to the trial of this Integrated Science Module product for junior high school students (junior high school) and equivalent. The research method used in this study is research and develompent method with ADDIE development model. The population is students of SMP Muhamadiyah Pabuaran, with suchrt scale research techniques. The instruments used are validation tests and student response tests in the form of questionnaires. Data analysis techniques use descriptive analysis techniques that calculate the percentage of validation values. The results of the study obtained an average score of 75% for media experts with the categories